Adiponectin levels and sleep deprivation in patients with endocrine metabolic disorders - Oliveira, Roseane Feitosa de (2018)
BACKGROUND: Sleep abnormalities are frequent in patients with endocrine metabolic disorders (EMD) such as arterial hypertension, diabetes and obesity. Adiponectin is a peptide largely secreted by adipocytes and has various properties e.g. anti-inflammatory, antioxidant, antiatherogenic, pro-angiogenic, vasoprotective and insulin-sensitizing. Adiponectin inversely relates to body weight and when its concentration decreases, the resistin concentration increases resulting in greater insulin resistance. OBJECTIVE: The objective of this study is to examine factors influencing adiponectin levels in a population with EMD. METHODS: This was a cross-sectional evaluation of 332 patients (18 to 80y) presenting arterial hypertension, pre-diabetes, diabetes, and/or obesity. Investigation included clinical evaluation of comorbidities, general blood tests and adiponectin measures (ELISA). Chronic sleep deprivation was determined if habitual sleep was <6 hours >4 days/week. RESULTS: Arterial hypertension (78.5%), type-2 diabetes (82.3%), and overweight (45.0%)/obesity (38.8%) were frequent. Patients with type-2 diabetes tended to have more chronic sleep deprivation (p=0.05). Adiponectin levels increased with age and were inversely correlated with sagittal abdominal diameter (p=0.04) and fasting insulin (p=0.001). Chronic sleep deprivation was associated with higher adiponectin concentration [OR=1.34; CI=1.13-1.58; p<0.005] and this was maintained after adjustment for gender, age, body mass index, menopause, arterial hypertension, American Diabetes Association classification and physical exercise levels [OR=1.38; CI=1.14-1.66: p=0.001]. CONCLUSION: In patients with EMD, adiponectin is influenced not only by obesity but also by age and sleep deprivation. The latter finding may be explained by a compensatory effect or a counter regulation to minimize the harmful effects of sleep deprivation.